2007
DOI: 10.1111/j.1525-1438.2006.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-based endometrial cytology: its possible value in postmenopausal asymptomatic women

Abstract: The incidence of endometrial adenocarcinoma in asymptomatic women is low. Nevertheless, some of these women might require endometrial surveillance. In this study, we evaluated the accuracy of liquid-based endometrial cytology compared to biopsy in asymptomatic postmenopausal women. Three hundred twenty women scheduled for hysteroscopy were enrolled for this study. After hysteroscopy, patients were submitted to endometrial cytology and to biopsy. Two hundred ninety-three (92%) women had sonographically thickene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 19 publications
2
36
0
5
Order By: Relevance
“…The main advantages of this procedure are the reduction in confounding factors, the distribution of cells on a thin layer and the possibility to obtain more slides from the same sample. The two LBP technologies currently in use include ThinPrep (Hologic Inc., Bedford, Mass., USA) and SurePath (BD Diagnostics, Burlington, N.C., USA) and several groups have reported their experience either by using ThinPrep [10,11,14,15] or SurePath [8,9,12,13] methods. There are subtle differences between ThinPrep and SurePath preparations which reflect different sampling devices, collection media and processing techniques [20,21,22,23].…”
Section: Processing Of Endometrial Lbp Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of this procedure are the reduction in confounding factors, the distribution of cells on a thin layer and the possibility to obtain more slides from the same sample. The two LBP technologies currently in use include ThinPrep (Hologic Inc., Bedford, Mass., USA) and SurePath (BD Diagnostics, Burlington, N.C., USA) and several groups have reported their experience either by using ThinPrep [10,11,14,15] or SurePath [8,9,12,13] methods. There are subtle differences between ThinPrep and SurePath preparations which reflect different sampling devices, collection media and processing techniques [20,21,22,23].…”
Section: Processing Of Endometrial Lbp Methodsmentioning
confidence: 99%
“…In fact, the LBP method enables storage of a variable amount of cells. Recently, several studies have described the cellular assessment of endometrial lesions by using cytoarchitectural criteria on LBPs [8,9,10,11,12,13,14,15]. The above described advantages of LBPs versus conventional slides suggest the replacement of conventional slides with LBPs in the routine cytologic evaluation of endometrial cell samples.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have described the usefulness of endometrial cytology for detecting endometrial carcinomas [9,10,11,12]. Moreover, screening tests using endometrial cytology for endometrial carcinomas may permit early detection and improve survival among patients with endometrial carcinomas [21].…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnostic accuracy for endometrial carcinoma has been reported to be more than 90% [9,10,11,12]. Several criteria or reporting systems have been developed to evaluate endometrial cytological features in conventional and liquid-based preparations [13,14,15] based on cellular atypia and morphological features.…”
Section: Introductionmentioning
confidence: 99%
“…1 It was recently reported that office endometrial sampling using suction endometrial curettage is effective for diagnosis, while being simple to perform and generally well tolerated by patients without requiring anaesthesia. [5][6][7][8][9][10][11][12][13][14] The purpose of the present study was to determine the best method for detecting endometrial cancer in outpatients with abnormal uterine bleeding. [2][3][4] In addition, endometrial cytology is reported to be less painful than suction curettage, but its diagnostic accuracy for endometrial carcinoma ranges quite widely from 70% to 98%.…”
Section: Introductionmentioning
confidence: 99%